Distinct Gut Virome Profile of Pregnant Women With Type 1 Diabetes in the ENDIA Study. (16th January 2019) - Wook Kim, Ki; Allen, Digby W; Briese, Thomas; Couper, Jennifer J; Barry, Simon C; Colman, Peter G; Cotterill, Andrew M; Davis, Elizabeth A; Giles, Lynne C; Harrison, Leonard C; Harris, Mark; Haynes, Aveni; et al.
Abstract: Background: The importance of gut bacteria in human physiology, immune regulation, and disease pathogenesis is well established. In contrast, the composition and dynamics of the gut virome are largely unknown; particularly lacking are studies in pregnancy. We used comprehensive virome capture sequencing to characterize the gut virome of pregnant women with and without type 1 diabetes (T1D), longitudinally followed in the Environmental Determinants of Islet Autoimmunity study. Methods: In total, 61 pregnant women (35 with T1D and 26 without) from Australia were examined. Nucleic acid was extracted from serial fecal specimens obtained at prenatal visits, and viral genomes were sequenced by virome capture enrichment. The frequency, richness, and abundance of viruses were compared between women with and without T1D. Results: Two viruses were more prevalent in pregnant women with T1D: picobirnaviruses (odds ratio [OR], 4.2; 95% confidence interval [CI], 1.0–17.1; P = .046) and tobamoviruses (OR, 3.2; 95% CI, 1.1–9.3; P = .037). The abundance of 77 viruses significantly differed between the 2 maternal groups (≥2-fold difference; P < .02), including 8 Enterovirus B types present at a higher abundance in women with T1D. Conclusions: These findings provide novel insight into the composition of the gut virome during pregnancy and demonstrate a distinct profile of viruses in women with T1D.